Metal-Organic Frameworks: Opportunities for Catalysis - Farrusseng, David; Aguado, Sonia; Pinel, Catherine (Angewandte Chemie (International ed.), 2009)
The role of metal-organic frameworks (MOFs) in the field of catalysis is discussed, and special focus is placed on their assets and limits in light of current challenges in catalysis and green chemistry. Their structural and dynamic features are presented in terms of catalytic functions along with how MOFs can be designed to bridge the gap between zeolites and enzymes. The contributions of MOFs to the field of catalysis are comprehensively reviewed and a list of catalytic candidates is given. The subject is presented from a multidisciplinary point of view covering solid-state chemistry, materials science, and catalysis.